Kegiatan IBM Goes to School Meningkatkan Pengetahuan Kewirausahaan pada Siswa SMA Tri Karya Surabaya - Sitepu, Sri Nathasya Br; Laijran, Darryl Abraham (Universitas Nusantara PGRI Kediri, 2023)
Tri Karya High School provides theoretical entrepreneurship or entrepreneurship learning. The impact of the theoretical learning of Tri Karya SMA students is that they are not confident and have low ability to explore business potential in themselves. This is because entrepreneurship or entrepreneurship subjects are not equipped with the effective bird-in-hand concept. The IBM Goes to School activity provides entrepreneurship training with the effective bird in hand concept. The training methods are in the form of presentation, question and answer sessions, group discussions, practice, and reflection. The result of the IBM Goes to School activity by using the effective bird in hand concept can maximize the quality of entrepreneurship or entrepreneurship learning for Tri Karya High School students. Tri Karya High School students become confident, able to arrange bird in hand from national/international entrepreneurs as well as individual bird in hand. The IBM Goes to School activity also provides entrepreneurship or entrepreneurship learning innovations in the form of practical methods and interactive discussions.